(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
To perform a sub-chronic toxicity study and to generate scientific data regarding the safety profile of T-AYU-HMTM Premium, a herbo-mineral formulation used for sickle cell disease. Experimental animals (Mice) were divided into six groups and were acclimatized and treated with 125 mg T-AYU-HMTM Premium/kg body weight (T1 LD), 625 mg T-AYU-HMTM Premium/kg body weight (T2 MD), and 1250 mg T-AYU-HMTM Premium/kg body weight (T3 HD) and two group of satellite daily for 90 days. 0.5% CMC was administered to the control group as a vehicle. The satellite groups were treated with 125 mg T-AYU-HMTM Premium/kg body weight (S1 LD) & 1250 mg T-AYU-HMTM Premium/kg body weight (S2 HD, 1250 mg/kg) receiving low & high dose respectively. The mice were closely observed for a clinical sign of toxicity, stereotypical behavior and alteration in autonomic activity during the entire study period. Hematological and blood biochemical parameters were observed on days 0, 60, 90. Motor coordination activity and sensory stimuli assessment were performed after the 11th week. At the termination of the study, all animals were sacrificed, and organs such as the heart, brain, kidney, liver, etc., were collected & observed for histopathology. There was no change in the normal gross behavior of animals in the sensory and motor assessment activity in the treatment group compared to the control group. Evaluation of hematological parameters shows a significant increase in red blood corpuscles. Histopathological examination of various organs shows a normal architecture in all the treated groups. T-AYU-HMTM Premium was found to be safe on repeat dose oral administration in NOAEL, dose up to 1250 mg/kg body weight when administered orally for 90 days in both the sexes of Swiss Albino mice.